2009
DOI: 10.1038/tpj.2009.69
|View full text |Cite
|
Sign up to set email alerts
|

A TOMM40 variable-length polymorphism predicts the age of late-onset Alzheimer's disease

Abstract: The ɛ4 allele of the apolipoprotein E (APOE) gene is currently the strongest and most highly replicated genetic factor for risk and age of onset of late-onset Alzheimer's disease (LOAD). Using phylogenetic analysis, we have identified a polymorphic poly-T variant, rs10524523, in the translocase of outer mitochondrial membrane 40 homolog (TOMM40) gene that provides greatly increased precision in the estimation of age of LOAD onset for APOE ɛ3 carriers. In two independent clinical cohorts, longer lengths of rs10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
406
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(447 citation statements)
references
References 45 publications
34
406
6
1
Order By: Relevance
“…26 Linkage with APOE is such that the APOE E4 allele is almost always linked to a long poly-T repeat, whereas the APOE E3 allele is linked to either a short or a very long poly-T repeat. 27 Relevant to the present study, longer TOMM40 poly-T repeats have been associated with an earlier onset of Alzheimer's disease. 27 It has been suggested that the risk of Alzheimer's disease in APOE E3 carriers with a very long TOMM40 poly-T repeat might equal, or even exceed, the risk generally associated with the APOE E4 allele.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…26 Linkage with APOE is such that the APOE E4 allele is almost always linked to a long poly-T repeat, whereas the APOE E3 allele is linked to either a short or a very long poly-T repeat. 27 Relevant to the present study, longer TOMM40 poly-T repeats have been associated with an earlier onset of Alzheimer's disease. 27 It has been suggested that the risk of Alzheimer's disease in APOE E3 carriers with a very long TOMM40 poly-T repeat might equal, or even exceed, the risk generally associated with the APOE E4 allele.…”
Section: Introductionsupporting
confidence: 68%
“…27 Relevant to the present study, longer TOMM40 poly-T repeats have been associated with an earlier onset of Alzheimer's disease. 27 It has been suggested that the risk of Alzheimer's disease in APOE E3 carriers with a very long TOMM40 poly-T repeat might equal, or even exceed, the risk generally associated with the APOE E4 allele. 26 It is not known whether the TOMM40 poly-T variants might also have a role in nonpathological cognitive decline.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…67 For example APOC1 and TOMM40 have been associated with increased risk of AD development 68 or earlier age of AD onset. 69 Large population samples would be needed to study the contribution of other genes to WM structure and AD.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…However, some researchers contend that variants of other genes in the APOE region play a role in AD development. For example, the mitochondrial cascade hypothesis holds that TOMM40 plays a role in AD development through the regulation of mitochondrial biogenesis (Roses et al., 2010; Swerdlow, Burns & Khan, 2014). NECTIN2 , which flanks TOMM40 , encodes a plasma membrane component of adherens junctions that also serves as an entry mediator for certain mutant strains of herpes simplex virus.…”
Section: Introductionmentioning
confidence: 99%